Associations of the severity of carotid and subclavian atherosclerosis with the conventional risk factors, clinical and angiographic variables in patients with acute coronary syndrome - L. L. Bershtein; M. D. Lunina; D. S. Evdokimov; T. V. Nayden; V. E. Gumerova; I. N. Kochanov; A. A. Ivanov; S. A. Boldueva; E. D. Resnyanskaya; E. V. Zbyshevskaya; A. E. Evtushenko; V. Kh. Piltakyan; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To characterize the association between cardiovascular risk factors and clinical and paraclinical variables with the severity of concomitant carotid and subclavian atherosclerosis in patients with acute coronary syndrome (ACS).Material and methods. Patients with ACS of any type, having obstructive coronary artery disease (CAD) confirmed by coronary angiography, underwent an ultrasound of the carotid and subclavian arteries with quantitative plaque assessment. The most important clinical, echocardiographic, angiographic and laboratory variables that contribute to atherosclerosis and/or affect the cardiovascular prognosis were evaluated. In patients with ACS considered ad the CAD onset, retrospective calculation of Systematic Coronary Risk Evaluation2 (SCORE2) score was performed.Results. A total of 312 patients aged 64 (56, 72) years (male, 69,2%) were studied. The detection rate of carotid/subclavian plaque was 86% and was higher in patients with more severe CAD — 79,4, 87,0, 92,6% in patients with 1-, 2- and 3-vessel disease respectively (p=0,027). However, 20% of patients with 2-/3-vessel CAD had no carotid/ subclavian atherosclerosis. Most of the traditional cardiovascular risk factors and other studied echocardiographic, angiographic, laboratory variables, as well as SCORE2 in patients with CAD onset did not demonstrate independent association with the severity of carotid/ subclavian atherosclerosis. The variability of the total plaque area (TPA) was explained by related multifactor regression model only to a small extent, R2=13%. Age (β 0,76, 95% CI 0,24-1,29, p=0,004), glomerular filtration rate (β -0,44, 95% CI -0,76 — -0,13, p=0,006); peripheral artery disease (β 19,50, 95% CI 1,63-37,37, p=0,033) demonstrated a significant independent association with TPA.Conclusion. In patients with ACS, only age, glomerular filtration rate and history of peripheral artery disease demonstrated the independent associations with carotid/subclavian atherosclerotic burden. Assessed variables explained 13% of TPA variability.